Analysis of airborne fungi in a hospital in the town of Ariquemes, Rondônia, Western Amazon region, Brazil - Jéssica Guimarães Pereira; Renato André Zan; Cacilda de Figueiredo Jardin; Dionatas Ulises de Oliveira Meneguetti (Universidade de Santa Cruz do Sul, 2014)
Backgound and Objectives: The hospital internal air environment is strongly associated with nosocomial fungal infections. In order to investigate the presence of hospital airborne fungi in one of the hospitals in the town of Ariquemes, Rondônia, air samples were collected in open Petri dishes between 15 to 30 minutes, containing the universal culture medium for fungi and yeasts: Saboraund agar, in the morning and afternoon, during October 2012 in the Surgical Center, Materials Center, Minor Surgery Room, Nursing Station and Hospital Admission Room. The isolated colonies underwent macroscopic analysis and subsequently the microculture technique to demonstrate the presence of airborne pathogens. Fifty colonies were isolated and 12 fungal genera were identified. All sectors showed the presence of fungi, which emphasizes the need for microbiological monitoring, especially in rooms with infection prophylaxis priority.